Informal Health Provider and Practical Approach to Lung Health interventions to improve the detection of chronic airways disease and tuberculosis at primary care level in Malawi: study protocol for a randomised controlled trial. Issue 1 (December 2015) - Banda, Hastings; Mortimer, Kevin; Bello, George; Mbera, Grace; Namakhoma, Ireen; Thomson, Rachael; Nyirenda, Moffat; Faragher, Brian; Madan, Jason; Malmborg, Rasmus; Stenberg, Berthe; Mpunga, James; et al.
Abstract Background In developing countries like Malawi, further investigation is rare after patients with chronic cough test negative for tuberculosis. Chronic airways disease has presentations that overlap with tuberculosis. However, chronic airways disease is often unrecognised due to a lack of diagnostic services. Within developing countries, referral systems at primary health care level are weak and patients turn to unskilled informal health providers to seek health care. Delayed diagnosis and treatment of these diseases facilitates increased severity and tuberculosis transmission. The World Health Organisation developed the Practical Approach to Lung Health strategy which has been shown to improve the management of both tuberculosis and chronic airways disease. The guidelines address the need for integrated guidelines for tuberculosis and chronic airways disease. Engaging with informal health providers has been shown to be effective in improving health services uptake. However, it is not known whether engaging community informal health providers would have a positive impact in the implementation of the Practical Approach to Lung Health strategy. We will use a cluster randomised controlled trial to determine the effect of using the two interventions to improve case detection and treatment of patients with tuberculosis and chronic airways disease. Methods A three-arm cluster randomised trial design will be used. A primary health centre catchment population will form a cluster, which will be randomly allocated to one of the arms. The first arm personnel will receive the Practical Approach to Lung Health strategy intervention. In addition to this strategy, the second arm personnel will receive training of informal health providers. The third arm is the control. The effect of interventions will be evaluated by community surveys. Data regarding the diagnosis and management of chronic cough will be gathered from primary health centres. Discussion This trial seeks to determine the effect of Informal Health Provider and Practical Approach to Lung Health interventions on the detection and management of chronic airways disease and tuberculosis at primary care level in Malawi. Trial registration The unique identification number for the registry is PACTR201411000910192 – 21 November 2014